2014
DOI: 10.1159/000366396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of RhoGDI2 Mediated Lung Cancer Epithelial-Mesenchymal Transition Suppression

Abstract: Background: The aim of this study was to evaluate the function of RhoGDI2 in lung cancer epithelial-mesenchymal transition (EMT) process and to illustrate the underlying mechanisms that will lead to improvement of lung cancer treatment. Methods: The RhoGDI2 knock-down and overexpressing A549 cell lines were first constructed. The influence of RhoGDI2 on cytoskeleton in A549 cells was studied using two approaches: G-LISA-based Rac1 activity measurement and immunostaining-based F-actin distribution. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Rho signaling governs actin redistribution [32-41] and is implicated in various cellular responses including cell-cell adhesion and EMT [13, 22, 25, 42-45]. In the present work, we reported opposite effects of the KDM2B gene in the expression of RhoA/RhoB/RhoC- and Rac1-GTPases.…”
Section: Discussionsupporting
confidence: 56%
“…Rho signaling governs actin redistribution [32-41] and is implicated in various cellular responses including cell-cell adhesion and EMT [13, 22, 25, 42-45]. In the present work, we reported opposite effects of the KDM2B gene in the expression of RhoA/RhoB/RhoC- and Rac1-GTPases.…”
Section: Discussionsupporting
confidence: 56%
“…The study showed that high expression of Rac1 induced EMT in tumor cells in vitro and in vivo 17, 18, and promoted invasion and metastasis of tumor. The inhibition of Rac1 expression significantly up-regulated the expression of E-cadherin, down-regulated the expression of N-cadherin and Vimentin, and significantly inhibited EMT in cancer cells 21. However, the correlation between Rac1 and EMT is still unclear in lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described 21, the main criterion of grouping was overall survival, calculated from the date of radiotherapy to the time of death (from any cause). The secondary criterion was local or distant recurrence rate.…”
Section: Methodsmentioning
confidence: 99%
“…Some NSCLCs are resistant to chemotherapy and radiation therapy, and are fast growing and highly invasive [1,2,3,4,5]. Thus, great efforts have been made to elucidate the mechanisms underlying the invasion and chemo-sensitivity of NSCLC [3,4,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%